Revealed Comparative Advantage (RCA) of Asean 5 Countries Watermelon in the Global Market - Saw Yan Naing; Masyhuri Masyhuri; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Watermelon Citrullus Lanatus (Thunb) is an important commercial fruit crop in ASEAN. One way to improve economic growth is through trade and comparative advantage. There are very some researches regarding with comparative advantage of watermelon trade in ASEAN. The purpose of this article is to determine the comparative advantage of watermelon trade in five ASEAN member countries. This article uses secondary data only. Watermelon trade data covering the six years period 2014-2019 were obtained from the United Nations Commodity Trade Statistics Database. This article applies the original index of the revealed comparative advantage (RCA) and revealed symmetric comparative advantage (RSCA) to find out the level of comparative advantage of watermelon commodity. Results show that Lao Peoples Democratic Republic, Myanmar and Viet Nam have a comparative advantage of watermelon trade in the global market. This study suggests that ASEAN 5 member nations should try to maintain its comparative advantage of watermelon exports in the international market.